Assessment of the use of tailings based on the legal requirements for radiation protection, from niobium mining in Minas Gerais – Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Brazil is the world's largest supplier of niobium to industry, accounting for 98% of world production, with Minas Gerais supplying 80% of total production. The mineral exploration industry generates millions of tons of waste annually. In several mining industries, waste is considered a burden for companies. Based on the radiation protection exemptions for the disposal of mining waste, the study analyses the use of waste as a raw material for the construction industry. The minimum dose rate found for gamma radiation in the waste was 0.24 µSv/h and a maximum dose of 0.33 µSv/h, which corresponds to an annual dose above the population exposure limit. The radio concentrations from gamma spectrometric analyses with the Ge(HP) detector for the two samples are a maximum of 240 Bq/kg for Ra-226 and a maximum of 840 Bq/kg for Ra-228. Despite the dose values determined for gamma radiation, CNEN Resolution 179 of 2014 considers materials with natural radioactive concentrations of radium 226 and 228 of up to 1000 Bq/kg suitable for use in the cement industry. Nevertheless, further analysis must be carried out. Since the tailings contain a concentration of Ra-226 and the radio is a source of radon gas, new analyses need to be carried out targeting the exhalation of radon.